DOS CURRÍCULOS À FORMAÇÃO DO CIENTISTA CONTÁBIL: cenários de reformas, inovações e formações - Ana Denise Ribeiro Mendonca Maldonado (2021)
This study is part of the research program of/in Observatório de Cultura Escolar (OCE), whose research objects and sources are curricular texts/documents produced for the spaces of formal and non-formal education. In this context, to insert ourselves into this program, we address the National Curriculum Guidelines (DCN), the United Nations/UNCTAD/ISAR world curriculum proposals, the curriculum proposals of the Federal Accounting Council (CFC), the data concerning the National Students Performance Exams (Enade) ratings of the last three editions and the Sufficiency Exams from the last three years. Thus, we proceed guided by the objective of characterizing the scenarios of reforms, innovations, and training included in the curricula of the accounting sciences courses with the highest scores of approval in the Sufficiency Exams, as well as those with excellent scores in the Enade, in addition to the proposals of the worldwide and national curriculum. The scope of this project encompasses, on the one hand, our choice for courses in the University of Brasilia (UnB) and the Commerce School-Foundation Álvares Penteado (FECAP), and on the other hand, the techniques of qualitative descriptive research, particularly bibliographic and documental analysis, in addition to the comparative study. The latter is a particular version of comparison procedures, named “comparative studies” (SILVA, 2016), organized as a particular version of the comparison methods, operated in the intersection of education, education history, and comparative sociology. Sequentially, we found that the texts/documents of the institutions analyzed can provide innovations in line with the DCN prescriptions, as well as the recommendations of the FBC/CFC and the ISAR/UNCTAD/United Nations, culminating in the training required by IFAC and AICPA, that is, the defense of a broad and consistent elementary/general education. Keywords: Accounting Sciences. Curriculum. Professional qualification. Reforms.